The first hypogean dipluran from Portugal: description of a new species of the genus Litocampa (Diplura: Campodeidae) - Reboleira, Ana Sofia P. S.; Sendra, Alberto; Gonçalves, Fernando; Oromí, Pedro (Zootaxa, 2010)
Knowledge of Portuguese Campodeidae is scant, with only 7 previous papers (Wygodzinsky 1944a; Condé 1951; Sendra 1990; Sendra & Moreno 2004, 2006; Gama et al. 2000a,b), with a total of 13 epigean species: Eutrichocampa Silvestri (1 sp.), Campodea Westwood (6 spp.) and Podocampa Silvestri (6 spp.). Three of these species are endemic to mainland Portugal: C. machadoi Condé, 1951, P. jorgei Wygodzinsky, 1944 and P. seabrai Wygodzinsky, 1944. Only one species, Podocampa cardini Silvestri, 1932, has been recorded from a Portuguese cave environment (Condé 1955); this species previously had been known as an epigean species from Sierra de Aralar in Navarra, Spain (Silvestri 1932). Intensive sampling efforts over the last four years in Portuguese karstic caves revealed the presence of a morphospecies originally assigned to Podocampa fragiloides Silvestri, 1932, which is often found in moist epigean environments of the Iberian Peninsula influenced by the Atlantic Ocean (A. Sendra, pers. obs.).